Lexical Cohesion Analysis on Adele’s Songs Lyrics in The Album 25 - Novi Eka Purnama Sari; Anindita, Widyashanti (Faculty of Language and Literature, University of Surakarta, 2020)
The objectives of this study are to identify the kinds of lexical cohesion used in Adele’s song lyrics in the album 25 and to find out the impact of the most type to hearers. This research is a descriptive qualitative research. Data analysis was performed by categorizing data based on the theory from Halliday and Hasan consisting of reiteration (repetition, synonym, superordinate, general word) and collocation. The final step is to present data and make conclusions. The research findings show that repetition has 34 data with 47%, followed by synonym has 15 data with 21%, superordinate and collocation have 9 data with 12% and general word has 6 data with 8%. Repetition dominates the lexical type of cohesion and general word is the least appear. The impacts of the most type to hearers are repetition makes the meaning of the song deeper and hearers will be deeper in enrolling their emoticons in the song.